Hypothèses céliniennes - PELLINI, Pierluigi (Firenze University Press, 2025)
The title of this book is not dictated by false modesty: in fact, the author aims to offer simple philological, linguistic and hermeneutical hypotheses. The subjects of these hypotheses are quite varied. They range from the enigma of Casse-pipe’s password to Céline’s relationship with naturalist models, and from the problems of editing the manuscripts retrieved in 2021 to the attempt to outline an original interpretation of Voyage au bout de la nuit.